Clinico-cytopathological subcategorization in thyroid nodules of atypia of undetermined significance/follicular lesion of undetermined significance using the TIRADS and Bethesda classifications - Babajani, Amirhesam; Rahmani, Saeed; Raoufi, Masoomeh; Eidgahi, Elham Shaarbaf; Dastjerdi, Amirreza Vahid; Behfarnia, Poya; Khalili, Shayesteh; Moghaddam, Noushin Afshar (Frontiers in Endocrinology, 2023)
Introduction: Bethesda category III – atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) is a heterogeneous class of the Bethesda system for thyroid nodules. In order to clarify the therapeutic road for clinicians, this category was subclassified based on the cytopathological features. In this study, we evaluated the risk of malignancy, surgical outcome, demographic characteristics, and correlation of ultrasound features with the final outcome in patients with thyroid nodules based on AUS/FLUS subclassification. Method: After evaluating 867 thyroid nodules from three different centers, 70 (8.07%) were initially diagnosed as AUS/FLUS. The cytopathologists re-interpreted the FNA samples and subclassified them into five subcategories: architectural atypia, cytologic atypia, cytologic and architectural atypia, and Hürthle cell AUS/FLUS, and atypia, which was not specified. Based on the suspicious ultrasound features, an appropriate ACR TI-RADS score was allocated to each nodule. Finally, the malignancy rate, surgical outcomes, and ACR TI-RADS scores were evaluated among Bethesda category III nodules. Results: Among the 70 evaluated nodules, 28 (40%) were subclassified as Hürthle cell AUS/FLUS, 22 (31.42%) as cytologic and architectural atypia, 8 (11.42%) as architectural atypia, 7 (10%) as cytologic atypia, and 5 (7.14%) as atypia which was not specified. The overall malignancy rate was 34.28%, and the architectural atypia and Hürthle cell nodules displayed lower malignancy compared to other groups (P-Value<0.05). Utilizing ACR TI-RADS scores showed no statistical significance between Bethesda III subcategorization and ACR TI-RADS scores. However, ACR TI-RADS can be a reliable predictor for Hürthle cell AUS/FLU nodules. Conclusion: ACR TI-RADS helps evaluate malignancy only in the Hürthle cell AUS/FLUS subcategory of AUS/FLUS. Besides, cytopathological reporting based on the suggested AUS/FLUS subclassification could help clinicians take appropriate measures to manage thyroid nodules.